2015
DOI: 10.12816/0027553
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effects of Human , Camel and Cow's Milk against Some Pathogenic Fungi in Iraq

Abstract: The present study investigates the use of the agar dilution method and the inhibitory effects of different concentrations (10%, 20% and 30%) of human, camel and cow's milk on thirteen different species of fungi from the genera Aspergillus, Trichophyton, Microsporum, Penicillium and Fusarium. The results show that all the tested concentrations of each of the three milks were capable of inhibiting the growth of the thirteen fungal species, but the greatest inhibitory effect was recorded with the concentration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…While SCU1 showed more variation than other isolates. Dates contain 75% sugars compared to other isolates, the presence of high concentration of sugar in the food medium leads to the formation of large amounts of alcohol even under the conditions of air, as the yeast is negatively affected by alcohol produced by the food medium [26,27]. These results are similar to a study [28,29,30].…”
Section: Resultssupporting
confidence: 85%
“…While SCU1 showed more variation than other isolates. Dates contain 75% sugars compared to other isolates, the presence of high concentration of sugar in the food medium leads to the formation of large amounts of alcohol even under the conditions of air, as the yeast is negatively affected by alcohol produced by the food medium [26,27]. These results are similar to a study [28,29,30].…”
Section: Resultssupporting
confidence: 85%
“…We all should have a role in preventing these infections and reducing antifungal resistance. [2,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…From genetic distance, the ratio of genetic similarity among the ten Trichophyton rubrum isolates from 0.97868 to 0.1025,showing Table (6).The highest similarity 0.97868 (99.8%) was obtained between isolates number (1 and 2)while 0.21556 (21.5%) genetic similarity between isolate number 3 and 6, but lowest level of similarity 0.1025 (10.2%) was appears between isolate number (5 and 7). During dendrogram were constructed based on [13]. Genetic distance using UPGMA cluster analysis and depicted genetic relationship among seven Trichophyton rubrum isolates showing two major cluster, first cluster contained two main distance, these were introduced from patients sources and isolate number 2 formed separated line that came from environmental sources, and second cluster contained isolate number (7,5) with lowest genetic similarity 0.1025.These isolates introduced from patients and environment sources, group, first group contain isolates number (1,2) with higher genetic similarity 0.9782.…”
Section: Issr-pcr Analysismentioning
confidence: 99%
“…It has been reported that the dendrogram generated by ISSR better with genealogy and the know pedigree of the ISSR than RAPD results, on the another hand, it has been found that the data on RAPD genetic distance have more relationship with the geographic distribution in comparative with ISSR data that based on number of chromosomes, ISSR markers are highly polymorphic and are useful in studies on genetic diversity [18,20]. Numbers of analysis studies used both ISSR and RAPD technique were found that ISSR produce more information with fewer number primer than number RAPD primer, during among study found a number polymorphic bands was still higher with less number [13,25,26]. ISSR less primers means less time, less DNA, less supplied and less samples, RAPD markers don't have the specific target comparing to ISSR markers.…”
Section: Issr-pcr Analysismentioning
confidence: 99%
See 1 more Smart Citation